2006
DOI: 10.1097/01.pgp.0000192274.44061.36
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Loss of Heterozygosity at 10q23.3 and Microsatellite Instability in Endometriosis, Atypical Endometriosis, and Ovarian Carcinoma Arising in Association With Endometriosis

Abstract: Genetic aberrations, such as loss of heterozygosity (LOH) and mutations leading to functional inactivation of the PTEN tumor suppressor gene, located on chromosome 10q23.3, have been shown to be associated with approximately one third of ovarian adenocarcinomas. In addition, microsatellite instability (MSI) leading to the functional inactivation of the PTEN gene has also been reported for ovarian adenocarcinomas with frequencies varying from 6 to 37%. However, the frequency of PTEN gene abnormalities has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…For example, hyperplastic polyps in colon are part of the distinct pathway of colorectal carcinogenesis characterized by MSI and deficiency in DNA MMR. Although the relationship between endometriosis and MSI has been controversial (6), a high frequency (~80%) of MSI was found in endometriosis and atypical endometriosis (14,25). In addition, methylation phenotype of hMLH1 gene (whose gene product is a component of the DNA MMR pathway) is correlated with microsatellite phenotype of MMR genes.…”
Section: Microsatellite Instability In CCCmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, hyperplastic polyps in colon are part of the distinct pathway of colorectal carcinogenesis characterized by MSI and deficiency in DNA MMR. Although the relationship between endometriosis and MSI has been controversial (6), a high frequency (~80%) of MSI was found in endometriosis and atypical endometriosis (14,25). In addition, methylation phenotype of hMLH1 gene (whose gene product is a component of the DNA MMR pathway) is correlated with microsatellite phenotype of MMR genes.…”
Section: Microsatellite Instability In CCCmentioning
confidence: 99%
“…Hypermethylation of hMLH1 is noted in ~10% of endometriosis (17). The high-level MSI or MSI leading to the PTEN dysfunction has also been reported for EOC with frequencies varying from 6 to 37% (14,25,35). Low-grade EAC are predominantly characterized by MSI.…”
Section: Microsatellite Instability In CCCmentioning
confidence: 99%
See 1 more Smart Citation
“…The PTEN gene encodes phosphatase, which inhibits apoptosis mediated by protein kinase B and participates in cellular signal transduction, leading to enhanced cell proliferation and survival. Sato et al (26) and Ali-Fehmi et al (31) detected LOH at 10q23.3 in 56.5 and 29% of endometriosis cases, respectively. In these studies, three specific loci on chromosome 10 were identified to exhibit the highest frequencies of LOH, leading to inactivation of the PTEN gene.…”
Section: Recent Progress In Endometriosis Research Using Capture Micrmentioning
confidence: 99%
“…Although LOH has been extensively investigated in ovarian cancer, this phenomenon has been rarely studied and is inconsistent in solitary endometriosis (17,(26)(27)(28)(29)(30)(31)(32)(33) (Table II). LOH at locus 10q23.3 is associated with phosphatase and tensin homolog (PTEN), which is one of the most studied TSGs (26,(30)(31)(32)(33)(34). The PTEN gene encodes phosphatase, which inhibits apoptosis mediated by protein kinase B and participates in cellular signal transduction, leading to enhanced cell proliferation and survival.…”
Section: Recent Progress In Endometriosis Research Using Capture Micrmentioning
confidence: 99%